PENGEMBANGAN ALAT EVALUASI KOGNITIF BERBASIS ISPRING SUITE 9 PADA MATERI LARUTAN PENYANGGA DI SMA NEGERI 9 KOTA BENGKULU - Pratiwi Kiki Ramadhanti; Wiwit Alwi; Febrian Solikhin (University of Bengkulu, 2023)
This research was a research and development to produce a cognitive evaluation tool based on iSpring Suite 9. The purpose of this study was to determine the feasibility of items and a cognitive evaluation tool based on iSpring Suite 9 on buffer solution material in terms of the assessment of material experts and media experts, knowing the validity empirical and reliability of the items on the cognitive evaluation tool based on iSpring Suite 9 on buffer solution material, and knowing the results of implementing the cognitive evaluation tool based on iSpring Suite 9 on buffer solution material in class XI MIPA 1 SMA Negeri 9 Bengkulu City. The development model used was the ADDIE development model which consists of analysis, design, development, implementation, and evaluation. This research was conducted at SMA Negeri 9 Bengkulu City with the research subjects being 10 students of class XI MIPA 1 for small-scale trials and 30 students of class XI MIPA 1 for field testing. The results obtained (1) the feasibility level of cognitive evaluation tools on the material aspect was 94.25% and from the media aspect was 90.83% or in the very feasible category, (2) based on the results of empirical validation obtained 20 valid items, (3) based on the reliability test obtained a coefficient of 0.951 which was included in the very high category, (4) based on the results of the implementation of the cognitive evaluation tool applied in the classroom, it was proven that it can be used to measure student learning outcomes with a mastery percentage of 83.3%. Keywords: cognitive evaluation tool, iSpring Suite 9, buffer solution